Effects of L-carnitine on performance of gestating and lactating sows - Musser, R.E.; Owen, K.Q.; Blum, S.A.; Civis, C.A.; Goodband, Robert D.; Tokach, Michael D.; Nelssen, Jim L.; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
A total of 307 sows was used to determine the effects of adding 50 ppm of L-carnitine in gestation and lactation diets on sow and litter performance. Addition of 50 ppm L-carnitine in gestation increased both total litter (34.1 vs 32.1 lb) and pig (3.48 vs 3.27 lb) birth weight. Litter weaning weights increased (99.03 vs 90.71 lb) when sows were fed added L-carnitine during gestation. Sows fed added L-carnitine in gestation had increased IGF-I concentrations on d 60 and 90 (71.3 vs 38.0, and 33.0 vs 25.0 ng/ml, respectively). These results suggest that feeding 50 ppm of added L-carnitine during gestation increases litter birth and weaning weights.
Keywords: Swine; L-Carnitine; Gestation; Birth weight